QIDANTONGMAI PROTECTS ENDOTHELIAL CELLS AGAINST HYPOXIA-INDUCED DAMAGE THROUGH REGULATING THE SERUM VEGF-A LEVEL - Wang, Bing; Wang, Wen; Li, Feng; Wang, Zongren; Ma, Jing; Zhao, Gang (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Qidantongmai (QDTM) is a Traditional Chinese Medicine (TCM) preparation that has long been used in folk medicine for the treatment of cardiovascular diseases. However, the underlying mechanisms are poorly understood. The present study was designed to determine the effects of QDTM on endothelial cells under hypoxic conditions both in vitro and in vivo. Primary human umbilical vein endothelial cells (HUVECs) were isolated, pretreated with QDTM medicated serum or saline control, and then cultured under hypoxia (2% oxygen) for 24 h. Sprague-Dawley rats were administered 1 ml/100 g of QDTM or saline twice a day for 4 days and treated with hypoxia (6 hours/day, discontinuous hypoxia, 360 mm Hg). QDTM not only protected HUVECs from hypoxia-induced damage by significantly retaining cell viability (P < 0.05) and decreasing apoptosis (P < 0.05) in vitro, but also protected liver endothelial cells from hypoxia-induced damage in vivo. Moreover, QDTM increased the serum VEGF-A level (P < 0.05) in rats treated with hypoxia for 7 days but suppressed the upregulation of serum VEGF-A in rats treated with hypoxia for 14 days. QDTM is a potent preparation that can protect endothelial cells against hypoxia-induced damage. The ability of QDTM to modulate the serum VEGF-A level may play an important role in its effects on endothelial cells.